Saeed, Abdul Jabbar. “The Frame of Reference for the Science of Hadith Textual Criticism,” Year 10, Issue 39 (Winter 1426 AH/ 2005 CE), Pp. 45-74. - سعيد, عبد الجبار (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2005)
Abdul Jabbar Saeed’s article addresses the importance of, and need for, hadith critique. It identifies the frames of reference for the science of hadith textual criticism, and diagnoses the methodological problems encountered by those interested in this science. The study utilizes a historical analytical method, referring to texts and traditional efforts of early scholars, and—through understanding and analyzing them—formulates frames of reference for hadith textual criticism. The study also uses an inductive method by collecting models of methodological errors often committed by those involved in hadith textual criticism and grouping them into similar groupings that expose aspects of methodological errors encountered by scholars in this field.